An Exploration of Challenges Facing Muslim Americans' Advancement to Leadership in the Legal Field. Issue 4 (January 2014) - Kadi, Ali S.
<x xml:space="preserve">Abstract</x> The purpose of this qualitative exploratory case study was to explore and identify obstacles that Muslim Americans in the United States working within the legal field experienced in advancing to leadership positions and to explore the influence of mentoring. The two cases included 10 Muslim Americans in leadership positions and 10 in nonleadership positions in the legal field in northern Virginia and Washington, D.C. Data were collected through structured and semi‐structured interviews, observations, and field notes. Themes and patterns were analyzed within and across data sources and cases for convergence, divergence, and triangulation. The results indicated that discrimination and the lack of opportunities, training, mentoring programs, support and guidance, and influential leaders hindered participants' advancement to leadership positions. Results revealed common major barriers to the lack of opportunity, social support, and understanding. The support and guidance of a mentor and degree attainment contributed to advancement. Leaders and nonleaders experienced similar obstacles to and supports for advancement. Lack of leadership experience was a barrier for nonleaders. The findings confirmed current literature on negative attitudes Muslim Americans face working and living in the United States following the September 11, 2001, terrorist attacks.